Perbedaan Prestasi Belajar Mahasiswa Ditinjau dari Jalur Seleksi Masuk Perguruan Tinggi - Anas Ma'ruf Annizar; Miftah Arifin (Universitas Indraprasta PGRI Jakarta, 2021)
The problem brought in this study is how the difference in student achievement is reviewed from the college entrance pathways. Based on that problem, this study aimed at determining whether or not there are differences in student achievement based on college entrance pathways. This study used a quantitative research approach, which included several hypothesis tests such as normality test, homogeneity test, anova test, and kruskall test. This research was conducted in 2020 with a sample of 1,215 students of IAIN Jember. The results showed that the Grade Point Average (GPA) of UMPTKIN students was significantly different, which was greater than the GPA of SPAN students and the GPA of Mandiri students class 2016-2017. For students of class 2017-2018, the GPA of UMPTKIN students was greater than the GPA of Mandiri students. For 2018-2019 students, the GPA of SPAN students was greater than the GPA of UMPTKIN students, and the GPA of UMPTKIN students was greater than that of Mandiri students. Whereas for 2019-2020 students, there was no significant difference between the 3 groups of students. From the data of 4 batches of students, it can be seen that students who entered through the Mandiri pathway have low achievement compared to the others. Meanwhile, students who entered through UMPTKIN and SPAN always compete to achieve their achievements.